Socialization and Waste Management in Reducing the Risk of the Spread of Dengue Hemorrhagic Fever (DHF) in Nolokerto Village, Kendal Regency - Putri Zulfikah; Dewi Sherly Banowati; Aenul Firliani Mutmainah; Fitria Kholbi Azizah; Wulan Maghfiroh Azzahra (Universitas Palangka Raya, 2024)
Dengue Hemorrhagic Fever (DHF) is one of the serious health problems in Indonesia, especially in areas with environmental conditions that support the breeding of Aedes aegypti mosquitoes. This research aims to provide counseling on health and waste management in an effort to reduce the risk of dengue transmission in Nolokerto Village. This service method is by conducting direct counseling at the Nolokerto Village Hall on August 3, 2024 and involving the local community. The results obtained show that intensive socialization and active community participation in environmental cleaning and waste management have a significant influence on the reduction of the number of dengue cases. The socialization carried out succeeded in increasing public awareness about the importance of maintaining environmental cleanliness as a measure to prevent dengue. In addition, good waste management, including waste segregation and the removal of mosquito breeding grounds, has proven effective in reducing the population of Aedes aegypti mosquitoes